EPP functionalised Na-montmorillonite by cation-exchange reaction: a novel facile fluorescent nanocomposite. (August 2013) - Feng, C; Mo, Z L; Xie, T T; Guo, R B
Abstract : A novel fluorescent nanocomposite material of Eu(III)-PAA-phen complex (EPP) inserted into the layers of Na-MMT by cation-exchange reaction was prepared in this work. Fourier transform infrared spectrometer (FTIR) analyses, X-ray diffraction (XRD), transmission electron microscopy (TEM), thermogravimetric (TG) analyses were used to character the microstructure of the nanocomposite samples. The results show that the composite materials with good thermal stability and fluorescence property have been successfully synthesised, dispersion effect of PAA matrices to Eu 3+ nuclear units can effectively inhibit the fluorescence quenching of solid complexes.